Precarious Japan - Allison, Anne 1950- (Duke University Press, 2013)
Introduction : pain of life -- From lifelong to liquid Japan -- Ordinary refugeeism : poverty, precarity, youth -- Home and hope -- The social body? : in life and death -- Spinning the edges -- In the mud
Includes bibliographical references and index. - Description based on print version record
Keywords: Armut; Prekariat; Japan